2009
DOI: 10.5194/angeo-27-2593-2009
|View full text |Cite
|
Sign up to set email alerts
|

Observation of mesospheric gravity waves at Comandante Ferraz Antarctica Station (62° S)

Abstract: Abstract. An airglow all-sky imager was operated at Comandante Ferraz Antarctica Station (62.1 • S, 58.4 • W), between April and October of 2007. Mesospheric gravity waves were observed using the OH airglow layer during 43 nights with good weather conditions. The waves presented horizontal wavelengths between 10 and 60 km and observed periods mainly distributed between 5 and 20 min. The observed phase speeds range between 5 m/s and 115 m/s; the majority of the wave velocities were between 10 and 60 m/s. The wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 18 publications
11
33
0
Order By: Relevance
“…In our observations at Ferraz Station during 2007, more than 230 gravity wave events were observed (Bageston et al, 2009). The report of only two wave front events (wall event reported by Bageston et al (2011) and the present study), among a large number of gravity wave events, confirms the low occurrence rate of bores at high southern latitudes compared to lower latitudes (Fechine et al, , 2009).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…In our observations at Ferraz Station during 2007, more than 230 gravity wave events were observed (Bageston et al, 2009). The report of only two wave front events (wall event reported by Bageston et al (2011) and the present study), among a large number of gravity wave events, confirms the low occurrence rate of bores at high southern latitudes compared to lower latitudes (Fechine et al, , 2009).…”
Section: Introductionsupporting
confidence: 61%
“…An exposure time of 20 s was used for each image, yielding a sampling interval of ∼38 s since the imager does not have a filter wheel. The original images (1024 × 1024 pixels) were not binned, but cropped to 512 × 512 pixels due to limitations of the optical system (Bageston et al, 2009, which produces a useful image inside of 312 × 312 pixels on the CCD. The quality of the airglow data and its usage were limited by weather conditions to clear sky and new moon periods.…”
Section: Airglow Measurementsmentioning
confidence: 99%
“…Bageston et al (2009) in their observations at Ferraz Station, during 2007, observed more than 230 gravity wave events, but only two clear cases of mesospheric fronts were reported. The first one was a mesospheric wall (Bageston et al, 2011a) and the second one was a mesospheric bore (Bageston et al, 2011b).…”
mentioning
confidence: 95%
“…Studies employing individual lidar or airglow instruments cannot quantify GW characteristics as fully as combinations of instruments that define horizontal and vertical GW structures and their environments together. Such studies have nevertheless contributed to our initial understanding of GW scales, periods, phase speeds, likely sources, and propagation directions [e.g., Taylor and Hapgood, 1988;Taylor et al, 1993Taylor et al, , 1995aTaylor et al, , 1997Collins et al, 1996;Nakamura et al, 1999;Hu et al, 2002;Bageston et al, 2009;Yue et al, 2009].…”
Section: Introductionmentioning
confidence: 99%